Uniform flow distribution type profiled sheeting and intercooler - JING XIAOPING; YANG HONGLIANG (2017)
The utility model provides an uniform flow distribution type profiled sheeting and intercooler belongs to the indirect heating equipment field, include the profiled sheeting main part, two profiled sheeting main parts overlappings set up and form the mobile passageway of confession medium, and the face of profiled sheeting main part is provided with the recess, and the tank bottom of recess is provided with the wall arch, and the opposite side interval setting that cuts off the length direction of arch and profiled sheeting main part forms and feeds through the groove, and the wall arch feeds through a passage partition formation flow groove and the 2nd flow groove, a flow groove and the 2nd flow groove through feeding through the groove, it is protruding to be provided with a plurality of diversions on a flow groove's the lateral wall, and it is protruding to be provided with a plurality of diversions on the 2nd flow groove lateral wall. After this uniform flow distribution type profiled sheeting assembly fo